1995
DOI: 10.2214/ajr.165.1.7785564
|View full text |Cite
|
Sign up to set email alerts
|

Duplex sonography after transjugular intrahepatic portosystemic shunts (TIPS): normal hemodynamic findings and efficacy in predicting shunt patency and stenosis.

Abstract: Consistent changes in portal venous and hepatic arterial hemodynamics are normally seen on duplex sonography after placement of a TIPS. Duplex sonography accurately predicts shunt patency and dysfunction when compared with portal venography. Duplex sonography is an effective, noninvasive method of evaluating shunt function and should be considered for use as the primary imaging technique in routine follow-up after TIPS placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
15

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 11 publications
3
70
0
15
Order By: Relevance
“…This finding was first described by Foshager et al, but no significant conclusion could be drawn because of the limited number of cases in which this parameter was studied (12). Middleton et al found that temporal change in flow direction is a strong indication for TIPS malfunction with PPV of 92% on the left and 86% in the right portal vein.…”
Section: Intrahepatic Portal Vein Flowmentioning
confidence: 86%
See 4 more Smart Citations
“…This finding was first described by Foshager et al, but no significant conclusion could be drawn because of the limited number of cases in which this parameter was studied (12). Middleton et al found that temporal change in flow direction is a strong indication for TIPS malfunction with PPV of 92% on the left and 86% in the right portal vein.…”
Section: Intrahepatic Portal Vein Flowmentioning
confidence: 86%
“…Maleux et al report carbon dioxide wedged hepatic venograpghy to be a safe, efficient and reliable for right and left portal vein opacification (15). Another proposed technique involves percutaneous placement of fluoroscopically visible intrahepatic Foshager et al reported a significant increase of the hepatic artery velocity after TIPS placement (12). Conditions in which the arterial blood supply can be insufficient include systemic atherosclerosis and liver transplant patients (Fig.…”
Section: Sonographic Assessment After Tips Placementmentioning
confidence: 99%
See 3 more Smart Citations